Marianna Gonçalves da Luz na história da educação maranhense: trajetória de uma professora negra do município de Itapecuru –Mirim (1871-1960) - MARTINS, Alberto Magno Moreira (2025)
This thesis deals with education in Maranhão, through the trajectory of a black teacher from the municipality of Itapecuru Mirim (1871-1960). It is part of the History and Politics of Education research line, developed in the History and Memory of Brazilian Education study group. This aims to analyze the educational, intellectual and professional trajectory of Marianna Gonçalves da Luz, with emphasis on her teaching knowledge, literary productions and her contributions to Itapecuruense society and to the History of Education in Maranhão, during the period of her experience, characterized by fundamental from the social, historical and feminist field; and its procedures include bibliographical review and the use of documentary sources. To support these studies we use the theoretical contributions of: Bourdieu (1996; 2006); Certeau (2002); Motta (2003); Perrot (2005); Nunes (2006); Louro (2008); Meihy: Holanda (2012); Souza (2012); Santana (2014); Reis (2017) and other scholars who focus on the topic, which will enable greater visibility of the Afro-descendant woman in the context of Brazilian society. The methodological approach will be anchored in the history of education, focusing on a subject of education and literature, specifically Marianna Gonçalves da Luz. The following categories are: trajectory; invisibility; black woman; poet and teacher, about which we agree with Franco (2008, p. 10) when stating that "they are perfectly possible and necessary for knowledge, through content analysis, within the scope of a critical methodological approach and epistemologically supported by the conception of science that recognizes the active role of the subject in the production of knowledge". The documentary analysis will include publications and iconographic materials from available public and private collections. The results obtained revealed that Marianna Gonçalves da Luz played a crucial role in the education of Itapecuru- Mirim, using methodologies adapted to local conditions and thus promoting social inclusion. His pedagogical practice was marked by an ethical and political commitment to education as a tool for social emancipation. Her literary production, although unintentionally, addressed relevant social issues, especially the living conditions of black populations and the inequalities faced by women, contributing to the construction of a more inclusive cultural memory. In conclusion, Marianna Gonçalves da Luz contributed significantly to the history of education in Maranhão through her work as a teacher and black writer in Itapecuru-Mirim in the first half of the 20th century. His dedication to education, defense of teachers' rights, literary production and cultural involvement contributed to social inclusion and the appreciation of Afro- descendant identity, leaving a legacy that continues to inspire and influence Maranhão society. . Hence, it is expected that the study will provide the expected contribution in the educational and literary field. In this way, by understanding the insertion of Marianna Gonçalves da Luz in the educational and cultural scene of Itapecuru-Mirim and Maranhão, we hope to contribute to the construction of a more inclusive and critical memory of the history of Brazilian education.